International Nurse Leaders' Journeys of Engagement, Belonging, and Growth in Professional Nursing Organizations: A Qualitative Study - Jihane Frangieh; Edmund J. Walsh; Kay Kennedy; Kim Crawford; Cindy Zellefrow; Beverly Hancock; Mary A. Dolansky (Journal of Nursing Scholarship, 2026)
ABSTRACT Introduction Professional nursing organizations play a central role in connecting nurse leaders across borders, advancing leadership science, and addressing shared challenges, including workforce sustainability, burnout, and policy influence. Little is known about how specialized professional nursing organizations with a primarily national membership base can build and sustain meaningful international membership. Barriers to and facilitators of international membership in professional nursing leadership organizations have received limited attention in the literature, particularly from the perspectives of international members themselves. The aims of the study are to explore the perspectives of international nurse leaders enrolled in the Association for Leadership Science in Nursing International Ambassador Program on what motivates and sustains their engagement, the leadership‐related benefits they seek, the organizational supports that would make engagement more feasible, and the contributions they bring as members of an international nursing leadership community. Design A qualitative descriptive design was used. Methods Data were collected using a Zoom‐based focus group with five of 11 nurse leader ambassadors enrolled in the program. Data were analyzed using Braun and Clarke's six‐phase reflexive thematic analysis. Trustworthiness was supported through investigator triangulation, peer debriefing, an audit trail, and reflexive review of researcher perspectives. Results Four themes were developed: (1) reciprocal exchange , in which members positioned themselves as contributors as well as recipients; (2) engaging on our own terms , framing access and context‐sensitivity as preconditions of membership; (3) belonging as more than membership , distinguishing formal affiliation from felt inclusion in a community of nurse leaders; and (4) growth through sustained international relationships, in which professional growth depends on ongoing cross‐border connection rather than time‐bound programs. Conclusion Findings suggest that international nursing leadership organizations should build infrastructure for reciprocal contribution, equitable access, substantive belonging, and sustained cross‐border relationships to engage and retain global members. Clinical Relevance Engagement in global nursing communities facilitates the exchange of knowledge, best practices, and innovations across healthcare settings. These opportunities can strengthen leadership development, support evidence‐based practice, and ultimately improve patient outcomes.